QTL Mapping in Crop Improvement: Present Progress and Future Perspectives - Wani, Shabir Hussain; Wang, Dechun; Pratap Singh, Gyanendra (Elsevier Science & Technology, 2022)
QTL Mapping in Crop Improvement: Present Progress and Future Perspectives presents advancements in QTL breeding for biotic and abiotic stresses and nutritional improvement in a range of crop plants.The book presents a roadmap for future breeding for resilience to various stresses and improvement in nutritional quality.